STRATEGI HUMAS PROTOKOL DPRD PROVINSI SULAWESI SELATAN DALAM MEMBANGUN MEDIA RELATIONS (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The focus of this research is the strategy used by the Protocol Public Relations of the DPRD of South Sulawesi Province in building media relations. The purpose of this study was to determine the protocol public relations strategy of the DPRD of South Sulawesi Province in building media relations as well as the advantages and disadvantages of the Protocol Public Relations of the DPRD of South Sulawesi Province in disseminating information. This research is qualitative in nature using a scientific communication approach. Sources of data in this study were the Head of Subdivision of Public Relations, Protocol and Publications, Public Relations staff, and two representatives from the mass media, and the public. The data collection method used is observation, interviews with five informants, and documentation. The research instruments are the researchers themselves with the help of interview guidelines, recording aids in the form of cellphones, and cameras. Furthermore, the data is processed by qualitative analysis through data reduction, data presentation, and drawing conclusions. The results of this study indicate that 1) the South Sulawesi Provincial DPRD Protocol Public Relations strategy in building media relations is to build equal partners, implement information disclosure in partnerships, use the principle of mutual benefit, and build a personal approach to the media. 2) The advantages of the Public Relations Protocol of the DPRD of South Sulawesi Province in disseminating information are a wide network with the media, open access to information for the public, and good service to the media. The weakness of the Protocol Public Relations of the DPRD of South Sulawesi Province in disseminating information is the lack of staff in the Protocol Public Relations of the DPRD of South Sulawesi Province.